Description of The Visual Image Magnification on Ginger Emulsion using Kappa and Iota Carrageenan - Rani Oktaviani Saraswati; Ahmad Ni'matullah Al-Baarri; Heni Rizqiati; Anang Mohamad Legowo; Yoyok Budi Pramono; Yoga Pratama; Masykuri masykuri (Journal of Applied Food Technology, 2019)
This study aimed to analyze the magnification of visual image upon SEM analysis for determining the optimum view in order to obtain proper information of SEM image in ginger emulsion. The treatment in this research are without carrageenan, with iota carrageenan and with kappa carrageenan. Emulsion of ginger Graphical display testing according to using the Scanning Electron Microscope (SEM) method. The research showed that ginger emulsion with and without carrageenan were able to be seen clearly and the particle size were able to detected at a range 0.5-5 µm. The sample with iota carrageenan provided the information of separation among particles and it could not be seen clearly on the sample with kappa carrageenan. The low magnification of 250 times provided beneficial information to obtain the environment of particle.